2011
DOI: 10.3171/2010.12.focus10282
|View full text |Cite
|
Sign up to set email alerts
|

Management of ossification of the posterior longitudinal ligament of the thoracic spine

Abstract: The management of thoracic ossification of the posterior longitudinal ligament has been studied by many spinal surgeons. Indications for operative intervention include progressive radiculopathy, myelopathy, and neurological deterioration. The ideal surgery for decompression remains highly debatable as various methods of surgical treatment of ossification of the posterior longitudinal ligament have been devised. Although numerous modifications to the 3 main approaches have been identified (anterior, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In their study, they found that many factors were accounting for poor outcome such as age, duration of symptoms, type of OPLL, location of OPLL, number of segments involved, coexistence of other degenerative conditions, comorbidities, preoperative neurology, type of approach used, and instrumented fusion. [24,25]…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they found that many factors were accounting for poor outcome such as age, duration of symptoms, type of OPLL, location of OPLL, number of segments involved, coexistence of other degenerative conditions, comorbidities, preoperative neurology, type of approach used, and instrumented fusion. [24,25]…”
Section: Discussionmentioning
confidence: 99%
“…An anterior approach may be preferable to remove T-OPLL, but the transthoracic/extraplerual approach or trans-sternal approach is technically challenging and is associated with a higher complication rate 4 16 18) . A recent review on this subject has shown that neurological deficit occurred in 2.7-18.8% of patients after an anterior approach 5 17 18) . Direct removal of the ossified mass with a posterior only approach may be an alternative, but it has been traditionally challenging secondary to associated kyphotic deformities, adhesion of T-OPLL to the dura and a narrow/blind surgical field 3 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Indirect decompression could be achieved with laminectomy, laminoplasty or posterior instrumented correction of thoracic kyphosis 5 8 11 12 13 14 15 18 26 27 28 30) . Although direct removal of T-OPLL is ideal for neural element decompression, complications associated with the anterior approach, e.g., neurologic deficit and dural tear/cerebrospinal fluid (CSF) leakage, leads us to explore other potential surgical options 5 13 14 17 18) . Because laminectomy had a poor outcome due to progression of thoracic kyphosis and persistent ventral compression, instrumented fusion with or without direct removal of T-OPLL mass with posterior approach was introduced with comparable recovery rate to anterior approach 5 9 11 12 13 14 18 19) .…”
Section: Introductionmentioning
confidence: 99%
“…The surgical field becomes wider as one chooses the approach from the former to the later, respectively, allowing better visualization, hence better ventral decompression, but with more tissue devitalization. [3][4][5][6][7][8] The transpedicular approach through a dorsal midline incision can achieve effective posterior decompression, posterolateral vertebrectomy, coupled with posterior transpedicular fixation even for multiple levels in a single session. This technique is familiar to many spine surgeons, and surely avoids the high morbidity complicating whether the anterior approach or the combined anterior and posterior approaches, hence it is considered an ideal approach for severely ill patients.…”
Section: Introductionmentioning
confidence: 99%